2009
DOI: 10.1200/jco.2008.21.1441
|View full text |Cite
|
Sign up to set email alerts
|

Health Behaviors, Medical Care, and Interventions to Promote Healthy Living in the Childhood Cancer Survivor Study Cohort

Abstract: A B S T R A C TChildhood cancer survivors are at risk for medical and psychosocial late effects as a result of their cancer and its therapy. Promotion of healthy lifestyle behaviors and provision of regular risk-based medical care and surveillance may modify the evolution of these late effects. This manuscript summarizes publications from the Childhood Cancer Survivor Study (CCSS) that have examined health behaviors, risk-based health care, and interventions to promote healthy lifestyle practices. Long-term su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
217
2
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(232 citation statements)
references
References 71 publications
10
217
2
3
Order By: Relevance
“…While a number of studies have reported adverse outcomes (Grant et al, 2006;Speechley et al, 2006;Stam et al, 2006;Reinfjell et al, 2009;Gurney et al, 2009;Nathan et al, 2009;Hudson et al, 2003;Mulhern et al, 2004;Oeffinger et al, 2008), others have concluded that QoL (Langeveld et al, 2002(Langeveld et al, , 2004Zebrack and Chesler, 2002;Shankar et al, 2005;Zeltzer et al, 2008Zeltzer et al, , 2009Servitzoglou et al, 2009;Sundberg et al, 2009) and psychosocial adjustment (Gray et al, 1992;Elkin et al, 1997;Noll et al, 1997;Patenaude and Kupst, 2005;Meyerowitz et al, 2008) are satisfactory for the majority of long-term childhood cancer survivors. Finally, a few studies have found that the prevalence of depression in survivors of childhood cancer equal that of healthy controls (Gray et al, 1992;Zebrack and Zeltzer, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…While a number of studies have reported adverse outcomes (Grant et al, 2006;Speechley et al, 2006;Stam et al, 2006;Reinfjell et al, 2009;Gurney et al, 2009;Nathan et al, 2009;Hudson et al, 2003;Mulhern et al, 2004;Oeffinger et al, 2008), others have concluded that QoL (Langeveld et al, 2002(Langeveld et al, , 2004Zebrack and Chesler, 2002;Shankar et al, 2005;Zeltzer et al, 2008Zeltzer et al, , 2009Servitzoglou et al, 2009;Sundberg et al, 2009) and psychosocial adjustment (Gray et al, 1992;Elkin et al, 1997;Noll et al, 1997;Patenaude and Kupst, 2005;Meyerowitz et al, 2008) are satisfactory for the majority of long-term childhood cancer survivors. Finally, a few studies have found that the prevalence of depression in survivors of childhood cancer equal that of healthy controls (Gray et al, 1992;Zebrack and Zeltzer, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…16 Thus, promoting the control of known cardiovascular risk factors, such as obesity, smoking, hypertension, diabetes, and lipid disorders is a crucial aspect of preventive strategies in the long-term follow-up of childhood cancer survivors. 17,18 Similar to childhood cancer survivors, YA cancer survivors have been found to be at high risk to die from malignant diseases followed by non-malignant causes of death such as circulatory and respiratory conditions. 7,11 After 20 years of follow-up, a recent study found a shift from malignancy as primary cause of death to non-malignant disease among survivors of YA cancer.…”
mentioning
confidence: 99%
“…20 In what refers to the specific malignancies, the most discussed in the literature were breast cancer 3,11,20,24,28,[38][39][40][41][42][43] and childhood cancer -lymphoma, leukemia, retinoblastoma and solid tumors. [44][45] In oncology context, the PICs are used in combination with chemotherapy and surgery and clinical cases with poor prognosis. 17,28 Looking for, thus, aiming healing, strengthening the immune system, minimizing the signs and symptoms of the disease, improving quality of life and the incentive to continue the conventional treatment.…”
mentioning
confidence: 99%
“…3,19,[22][23] It read, also, the use of such practices with the purpose to prevent recurrent cases of the disease. 40 It was found that the biological basis of therapy, with the use of herbal medicine, is the main practice used in cancer treatment, 4,16,19,28,34,[37][38]41,[44][45] then supplements and diet. [19][20]27,34,38,[41][42][44][45] It is seen from this perspective that, among the types of alternatives, that have been emphasized is the herbal medicine.…”
mentioning
confidence: 99%
See 1 more Smart Citation